(untitled) (Homoeopathy for All, 2025)
In today’s digital era, prolonged sitting, minimal physical activity, and poor dietary habits have become a part of everyday life. The increasing dependence on computers, smartphones, and desk based occupations has given rise to a sedentary lifestyle; one that predisposes individuals to a variety of health conditions, including piles or hemorrhoids. Long working hours, irregular eating patterns, stress, and digital fatigue have made this condition increasingly common among modern professionals.